Estudo da produção científica dos docentes de pósgraduação em Fonoaudiologia, no Brasil, para uma análise do domínio - Danuello, Jane Coelho [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Aiming at analyzing the domain of Speech, language and hearing science, in Brazil, a study on the scientific production of accredited teachers in post-graduation courses has been conducted, so as to provide a panoramic view in the field. Thus, specific goals were established encompassing aspects such as: geographic localization, date of publication, documental typology, collaboration dynamics, theme, and areas of knowledge. Eight post-graduation programs in the field, totaling 118 teachers, were identified in the country, through Capes, early in 2011. The data of their publications from 1979 (year in which the first post-graduation program in the field was created), in the formats of books, book chapters and journal articles, were extracted from their respective Lattes Curriculum, by using the scriptLattes tool, being manually complemented for the collection of key-words the teachers used most in their publications and the citations received for articles published. These data, as well as the adjacency matrices generated by scriptLattes, were organized through Excel, enabling the development of graphs and tables for analysis. The matrices were used in Ucinet to trace the networks and figure the indicators which describe their structure. The analysis shows that the courses are located in the South and Southeast regions of the country, mainly in the State of São Paulo. As to the typology of publications, a predominance of journal articles is seen in the publications of the teachers with the eight institutions, and in terms of evolution, their production shows, in general, a growing trend, despite occasional oscillations in volume. Co-authorship networks show that collaboration is, mainly, at the institutional level, being organized, frequently, according to theme preferences, with some teachers performing as a “bridge” among the others. Key-words analysis shows a diversity of topics covered in the field, involving issues related...

Com o objetivo de realizar uma análise do domínio da Fonoaudiologia, no Brasil, foi desenvolvido um estudo da produção científica dos docentes credenciados nos cursos de pós-graduação, visando oferecer uma visão panorâmica da área. Para tanto, foram estabelecidos os objetivos específicos, nos quais estão inseridos aspectos como: localização geográfica, data de publicação, tipologia documental, dinâmica de colaboração, temática, áreas do conhecimento. Por meio do portal da Capes, no início de 2011, foram identificados 8 programas de pós-graduação na área, contendo um total de 118 docentes. Os dados de todas as publicações desses docentes, a partir de 1979 (ano da criação do primeiro programa de pós-graduação da área), nos formatos de livros, capítulos de livros e artigos de periódicos, foram extraídos dos seus respectivos Currículos Lattes, utilizando a ferramenta scriptLattes, e complementados manualmente para a coleta das palavras-chave mais utilizadas pelos docentes em suas publicações e das citações recebidas pelos artigos publicados. Esses dados, assim como as matrizes de coautoria geradas pelo scriptLattes, foram organizados utilizando o Excel, possibilitando a elaboração de gráficos e tabelas para a análise. As matrizes foram utilizadas no Ucinet para traçar as redes e calcular os indicadores que descrevem a estrutura das redes. A análise revela que os cursos estão localizados nas regiões Sul e Sudeste do país, predominantemente no Estado de São Paulo. Quanto à tipologia das publicações, constata-se um predomínio dos artigos de periódicos nas publicações dos docentes das oito instituições; com relação à evolução da produção dos docentes, de modo geral, apresenta-se uma tendência crescente, ainda que, ocasionalmente, ocorram oscilações no volume de publicações. As redes de coautoria permitem verificar que a colaboração se dá, principalmente, em âmbito...
Keywords: Bibliometria; Fonoaudiologia; Pos-graduação; Publicações cientificas - Indicadores - Brasil